2020
DOI: 10.1038/s41396-020-00785-x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Firmicutes and Actinobacteria abundance in tomato rhizosphere causes the incidence of bacterial wilt disease

Abstract: Enrichment of protective microbiota in the rhizosphere facilitates disease suppression. However, how the disruption of protective rhizobacteria affects disease suppression is largely unknown. Here, we analyzed the rhizosphere microbial community of a healthy and diseased tomato plant grown <30-cm apart in a greenhouse at three different locations in South Korea. The abundance of Gram-positive Actinobacteria and Firmicutes phyla was lower in diseased rhizosphere soil (DRS) than in healthy rhizosphere soil (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
200
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(217 citation statements)
references
References 93 publications
15
200
1
1
Order By: Relevance
“…Importantly, we further found that isolates presumably related to keystone taxa have inhibitory effects on the pathogen and reduction of bacterial wilt disease incidence, highlighting the importance of keystone taxa in suppressing disease. Large numbers of previous studies have analyzed the soil microbial community, abundance, and diversity when bacterial wilt disease outbreak (Wang et al, 2017b;Qi et al, 2019;Wei et al, 2019;Lee et al, 2020). As they reported, we also found that the relative abundance of Firmicutes was higher in the suppressive soil compared to that in the conducive soil ( Figure 3A).…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, we further found that isolates presumably related to keystone taxa have inhibitory effects on the pathogen and reduction of bacterial wilt disease incidence, highlighting the importance of keystone taxa in suppressing disease. Large numbers of previous studies have analyzed the soil microbial community, abundance, and diversity when bacterial wilt disease outbreak (Wang et al, 2017b;Qi et al, 2019;Wei et al, 2019;Lee et al, 2020). As they reported, we also found that the relative abundance of Firmicutes was higher in the suppressive soil compared to that in the conducive soil ( Figure 3A).…”
Section: Discussionsupporting
confidence: 75%
“…This is consistent with the finding that Proteobacteria, Actinobacteria and Ascomycota are the most abundant phyla in plants and soil (24, 64). Actinobacteria is one of the bacteria whose dysbiosis in abundance in tomato rhizosphere causes the incidence of bacterial wilt disease (12).…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria is one of the bacteria whose dysbiosis in abundance in tomato rhizosphere causes the incidence of bacterial wilt disease (12).…”
Section: Hub Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an established concept of soil disease suppressiveness, which implies that natural soils can suppress the pathogens; however, this phenomenon varies and depends, among others, on cropping years, crop species, and soil types [3,4]. Generally, the soil is considered the disease-suppressive when it keeps most plants healthy, while the converse is true for the disease-conducive soil [5,6]. The adoption of some farm management and soil conservation practices such as using organic fertilizers, amendments, and crop rotation can enhance the soil disease suppressiveness [7,8].…”
Section: Introductionmentioning
confidence: 99%